Automatic construction of structural CAD models from 3D topology optimization. Issue 1 (2nd January 2018) - Cuillière, Jean-Christophe; François, Vincent; Nana, Alexandre
ABSTRACT: The integration of topology optimization (TO) methods with Computer-Aided design (CAD) arouses a growing interest for mechanical and structural design purposes. However, generating 3D optimized CAD models from raw TO results still remains a tedious task that requires significant experience and user input. This paper presents a fully automated process to generate 3D optimized CAD models from TO results that tend towards beam-like structures. Raw TO results are first derived into an optimized shape as a smooth triangulation. This triangulation is then derived as a curve skeleton, which is finally normalized to generate a CAD model composed with an assembly of standard structural straight beams. 3D beam structures obtained with this automatic process are validated through comparisons between FEA results obtained using mixed-dimensional FEA models and solid 3D tetrahedral FEA models. Efficiency of this automatic CAD model construction approach is demonstrated through applying it on several beam-like TO results. The TO method used in this work is the SIMP method but principles used could be extended to evolutionary (ESO/BESO) and other types of TO approaches. GRAPHICAL ABSTRACT: